Perlindungan Hukum Bagi Hoki Clean Shoes dalam Perjanjian Waralaba - Dwi Purnawan Dodik Saputra; Johannes Ibrahim Kosasih; Desak Gde Dwi Arini (Jurnal Preferensi Hukum, 2021)
The franchising is one of the business activities that support the economy. Therefore, in this study, this study analyzes the implementation of the franchise agreement clauses between franchisees and franchisees and knows the legal protection for Hockey Clean Shoes in case of default by the franchisee. This research uses empirical methods using document studies and field studies and data analysis using descriptive qualitative. The results show that the Hoki Clean Shoes franchise agreement has met the minimum clauses that must exist in the franchise agreement as stipulated in Government Regulation Number 42 of 2007 concerning Franchising and has fulfilled the principles of the agreement and is applicable in Indonesia. The obstacles faced by Hockey Clean Shoes so far are related to franchises because this is in the service sector so the turnover obtained by the franchisee every month is difficult for us to know because the financial management we do is different from the facts in the field. Franchise cooperation agreements like this are also vulnerable to default.